A worldwide bibliometric analysis of acromegaly in the past two decades: 1999–2022 - Peng, Shuqin; Liu, Qi; Teng, Yuanyuan; Huang, Biling; Liu, Ze; Li, Mingliu; Liang, Jieyu; Zhang, Yi; Wang, Min (Frontiers in Neuroscience, 2023)
Objectives To conduct a bibliometric analysis to quantify and identify the current status and trends of acromegaly research in the past two decades. Materials and methods Articles related to acromegaly that were published from 1999 to 2022 were retrieved through the Web of Science core collection (WoSCC) database. Then, they were imported into VOSviewer and CiteSpace to conduct a visualization analysis of authors, countries, institutions, citation numbers, cocitations, keywords, and references. Results A total of 3,909 articles were identified in the study. Among them, the United States made the largest contribution to the field. Moreover, Colao A. was the most prolific author, and the University of Naples Federico II was the institution with the most publications. In addition, the Journal of Clinical Endocrinology and Metabolism was the core journal in the field. High-frequency keywords mainly included “acromegaly,” “GH (Growth Hormone),” “IGH-I (Insulin-Like Growth Factor I),” “pituitary adenomas,” and “octreotide.” Conclusion Studies related to acromegaly have shown stable stepwise growth over the past two decades. Interestingly, the research focus after 2016 gradually shifted from the etiology, mechanism, medications for treatment, and complications to improving prognosis and quality of life of patients with acromegaly. The current findings may provide guidance for further research in the field of acromegaly.